Red Vienna: A Social Housing Experiment, 1923–1933 - Holzner, Mario; Huberman, Michael (The Journal of Interdisciplinary History, 2022)
The moderating effects of World War I on wealth and income inequality varied with the belligerents. In Austria, the state embraced austerity measures to eliminate hyperinflation and respect commitments to the League of Nations. To fill the void, the Social Democratic Workers’ Party (sdap) turned to its political stronghold in Vienna to advance its agenda of social spending and progressive taxation—Red Vienna’s signature program. The use of an electoral-cycle model finds that the construction of new buildings increased the party’s share of votes in municipal elections. The program mobilized support of young families in search of affordable and quality housing, also attracting the endorsement of the middle classes and elites, despite the higher tax burden imposed on them. The physical attributes of the new buildings and related investments, such as in schools, hospitals, and city infrastructure, benefited the entire population of Vienna.
Number: 1